2017
DOI: 10.1086/689820
|View full text |Cite
|
Sign up to set email alerts
|

Living on the Edge: Parasite Prevalence Changes Dramatically across a Range Edge in an Invasive Gecko

Abstract: Species interactions can determine range limits, and parasitism is the most intimate of such interactions. Intriguingly, the very conditions on range edges likely change host-parasite dynamics in nontrivial ways. Range edges are often associated with clines in host density and with environmental transitions, both of which may affect parasite transmission. On advancing range edges, founder events and fitness/dispersal costs of parasitism may also cause parasites to be lost on range edges. Here we examine the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
2
20
0
1
Order By: Relevance
“…It is generally thought that the location of a host and subsequent attachment by a dodder are mainly induced by changes in light quantity and quality rather than by volatile chemical cues from host plants 9,10 . Cuscuta seedlings conspicuously grow toward conditions with low red light:far-red light (R:FR) ratios, which are associated with denser canopy environments 9,10 , so the probability of encountering and parasitizing a host plant is much greater for dodder seedlings, which is consistent with previos results that the spread of parasites is mainly driven by host density 11,12 . Furthermore, parasites often prefer hosts with higher nutrient contents, especially nitrogen (N) (such as legumes) as N content is important in parasite performance, although it is not always better on nutrient-rich plants 1316 .…”
Section: Introductionsupporting
confidence: 72%
“…It is generally thought that the location of a host and subsequent attachment by a dodder are mainly induced by changes in light quantity and quality rather than by volatile chemical cues from host plants 9,10 . Cuscuta seedlings conspicuously grow toward conditions with low red light:far-red light (R:FR) ratios, which are associated with denser canopy environments 9,10 , so the probability of encountering and parasitizing a host plant is much greater for dodder seedlings, which is consistent with previos results that the spread of parasites is mainly driven by host density 11,12 . Furthermore, parasites often prefer hosts with higher nutrient contents, especially nitrogen (N) (such as legumes) as N content is important in parasite performance, although it is not always better on nutrient-rich plants 1316 .…”
Section: Introductionsupporting
confidence: 72%
“…Morphological divergence of dispersal‐related traits in vanguard populations has been observed in amphibians, for example in Australia with the invasive cane toad ( Rhinella marina ) and in France with the invasive African clawed frog ( Xenopus laevis ) (Phillips et al ., ; Louppe, Courant & Herrel, ). Similarly, reduced parasite prevalence in range‐edge populations has been demonstrated with the blue striped snapper ( Lutjanus kasmira ) in Hawaii and the common house geckos ( Hemidactylus frenatus ) in Australia (Gaither et al ., ; Coates et al ., ). In both cases there is a clear decrease in parasite prevalence moving from core, intermediate, to range‐edge populations.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, it has been found that parasite load varies according to habitat type, as a result of the environmental suitability for the parasite (Bulté et al 2009, Rubio andSimonetti 2009). In this regard, parasitism rate widely oscillates not only between individuals of the same species due to factors related to health condition (i.e., infection susceptibility or ability to defend against infection through immune system) (Folstad and Karter 1992) or behavioral avoidance (Hart 1990), but also between populations due to the differences in environmental conditions where each population inhabits (Coates et al 2017).…”
Section: Introductionmentioning
confidence: 99%